The Implementation of Product Diversification, Discount, Store Atmosphere Towards Consumer’s Buying Interest - Andrian Andrian; Pratiwi Nilasari (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2022)
This study aims to determine and examine the effect of product variables, price discount, and store atmosphere on buying interest. This research uses quantitative research methods. Collecting data in this study through the distribution of questionnaires to visitors to D’Cika Cakes and Bakery Jatibening Branch. The sample in this study amounted to 100 respondents. The sampling technique used is multiple linier regression. The results of this study indicate that product variables, price discount and store atmosphere partially and significantly can positively influence consumer buying interest. Based on the Coefficient of Determination Test (KD) that the adjusted R square value is 0.469 (46.9%). the three independent variables, namely Product Diversification (X1), Price Discounts (X2), and Store Atmosphere (X3) in this study were able to explain 46.9% of the dependent variable.